Behind The Wickedness: Portrayal of Villains in Children's Movies - Al Adawiah, Robi’ah Aldiini; Aulia, Zulfa Najwa; 'Aisy, Choirum Miftah Rihhadatul; Zahrani, Nanda Aulia; Tasyarofa, Asya Aldiini (Anaphora : Journal of Language, Literary, and Cultural Studies, 2024)
Children’s movies showed various characters in their movies. One of the concerns in creating stories for children was the portrayal of the villains. Therefore, the research problem of this study was to discussed the villain portrayal of three different home productions, such as Disney Animation Studios, Pixar Animation Studios, and Sony Pictures Animation. The movies from each home production were Namaari in Raya and the Last Dragon, Syndrome in The Incredibles (2004), and Chester V in Cloudy with a Chance of Meatballs 2. This study aimed to find a significant function of villains which were divided into male and female villain traits based on the theory by Holder-Freeman (2012) and also proairetic decoding based on theory by Nikolajeva (2010). This study filled the gap by concentrating on examining female and male gender stereotypes through the visual representation of understanding from their reading (Nikolajeva, 2010). Techniques of analysis by Spradley (1980) were employed in this study. This research employed descriptive qualitative design in which the data were acquired in the form of textual and visual. The results of this study showed that Namaari had complex villain traits, there were male and female traits, Syndrome, and Chester V fulfilled the male traits. While in proairetic decoding, there were dialogues that used only abstract words, dialogues that used only concrete words, and dialogues that used both abstract and concrete words. This study can be used as a basis for compiling a rubric whether the films are suitable for children or not. Besides for movies, this study may be preferred as a reference for further studies since it implemented theories that can be used for various literary works such as novels, illustrated books, and games.